2017
DOI: 10.1152/ajpendo.00396.2016
|View full text |Cite
|
Sign up to set email alerts
|

Mice with hyperbilirubinemia due to Gilbert’s syndrome polymorphism are resistant to hepatic steatosis by decreased serine 73 phosphorylation of PPARα

Abstract: Gilbert's syndrome in humans is derived from a polymorphism (TA repeat) in the hepatic gene that results in decreased conjugation and increased levels of unconjugated bilirubin. Recently, we have shown that bilirubin binds directly to the fat-burning nuclear peroxisome proliferator-activated receptor-α (PPARα). Additionally, we have shown that serine 73 phosphorylation [Ser(P)] of PPARα decreases activity by reducing its protein levels and transcriptional activity. The aim of this study was to determine whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 75 publications
(115 citation statements)
references
References 59 publications
3
112
0
Order By: Relevance
“…We have previously demonstrated that hepatocyte-specific loss of BVRA results in exacerbation of hepatic steatosis and insulin resistance in response to a chronic HFD through alterations in PPARα [21]. Activation of heme oxygenase-1 (HO-1) has beneficial effects to prevent fatty liver disease [15,31,70,71], which is most likely mediated by BVRA production of bilirubin [15,21,28,72]. Others have shown that heme-derived metabolic signals dictate immune responses [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that hepatocyte-specific loss of BVRA results in exacerbation of hepatic steatosis and insulin resistance in response to a chronic HFD through alterations in PPARα [21]. Activation of heme oxygenase-1 (HO-1) has beneficial effects to prevent fatty liver disease [15,31,70,71], which is most likely mediated by BVRA production of bilirubin [15,21,28,72]. Others have shown that heme-derived metabolic signals dictate immune responses [21].…”
Section: Discussionmentioning
confidence: 99%
“…Samples were collected under light isoflurane anesthesia via the orbital sinus. The fasting glucose levels were measured using an Accu-Chek Advantage glucometer (Roche, Mannheim, Germany) and fasting insulin levels were measured by ELISA (Ultrasensitive Mouse Insulin Kit, Crystal Chem, Elk Grove Village, IL, USA) as previously described [22,26,[28][29][30][31].…”
Section: Fasting Glucose and Insulinmentioning
confidence: 99%
“…Bilirubin was recently reported to act as a ligand for the peroxisome proliferator-activated receptor-alpha increasing its transcriptional activity. 11 This may have possible clinical relevance because the protection from high-fat diet-induced hepatic steatosis and insulin resistance due to increased peroxisome proliferatoractivated receptor-alpha activity were reported on the novel GS mouse model. 11 Based on these observations, bilirubin seems to act as a real endocrine molecule.…”
Section: Bilirubin Protective Role Molecular Mechanismsmentioning
confidence: 99%
“…Although toxic concentrations of bilirubin induce ER stress, milder elevations of bilirubin concentrations attenuate ER stress. Bilirubin was recently reported to act as a ligand for the peroxisome proliferator‐activated receptor‐alpha increasing its transcriptional activity . This may have possible clinical relevance because the protection from high‐fat diet–induced hepatic steatosis and insulin resistance due to increased peroxisome proliferator‐activated receptor‐alpha activity were reported on the novel GS mouse model .…”
Section: Bilirubin Protective Rolementioning
confidence: 99%
“…Once activated, PPAR α regulates genes that encode for mitochondrial and peroxisomal β -oxidation, which reduces dyslipidemia. In addition, activated PPAR α functions to hinder hepatic fatty acid synthesis through inhibition of FAS and SREBP1 and therefore lower lipid levels [21, 79, 80]. Dual agonists are a class of drugs that activate both PPAR α and PPAR γ , thereby combating diabetes mellitus and the metabolic syndrome among patients diagnosed with both conditions [81].…”
Section: The Impact Of Dual-acting Ppar Agonistsmentioning
confidence: 99%